Information literacy and news libraries: the challenge of developing information literacy instruction programs in a special library environment - Bradley, Fiona (Curtin University, 2003)
This study examines the current situation of training provided to journalists by news librarians in the United States and Australia. The study examines the factors affecting the provision of training and the potential for information literacy instruction to comprise most of the training provided. The definition of information literacy was explored in the context of journalists and news organisations. The study questions the adaptability of the concept to a workplace environment, where organisational and individual development is important. The results of a self-administered questionnaire are presented. Respondents indicated that news librarians are very willing to plan and conduct training, a clear majority agreeing that they should train journalists to search for their own information. Respondents also expressed a need for more training themselves with regard to the skills needed to deliver instruction. The results also found that training is at an early stage in news libraries, with few hours available for planning and conducting training, and mixed success with different training methodologies. A model is suggested as a method of selecting information literacy competencies for individual journalists. The model describes the relationships between individual, organisation, and occupation determined competencies. The study also discusses the implications of the lack of workplace training for journalists, which has impacted upon news libraries' ability to introduce training services. News librarians are providing training, and are pro-active in providing services and information to journalists, but managers do not yet recognise this as a major role for librarians in news organisations.Information literacy instruction needs to become an organisational goal in order to succeed. The difficulties of assessing and evaluating information literacy instruction in the workplace are outlined. The need for measurable outcomes and preevaluation in training are emphasised. Several considerations for further research are detailed, including the need for further clarification of the nature of information literacy in the workplace, as well as the relationship between the role of information literacy instruction in formal university education and the workplace.